Current trends in the management of degenerative lumbar spondylolisthesis. Issue 5 (May 2018) - Ferrero, Emmanuelle; Guigui, Pierre
Abstract : Degenerative spondylolisthesis (DS) is a common disease of the degenerative spine, often associated with lumbar canal stenosis. However, the choice between the different medical or surgical treatments remains under debate. Preference for surgical strategy is based on the functional symptoms, and when surgical treatment is selected, several questions should be posed and the surgical strategy adapted accordingly. One of the main goals of surgery is to improve neurological symptoms. Therefore, radicular decompression may be necessary. Radicular decompression can be performed indirectly through interbody fusion or interspinous spacer. However, indirect decompression has some limits, and the most frequent technique is a posterior decompression with fusion. Indeed, in cases of DS, associated fusion or dynamic stabilization are recommended to improve functional outcomes and prevent future destabilization. Risk factors for destabilization, such as anteroposterior and angular mobility, and significant disc height, have been discussed in the literature. When fusion is performed, osteosynthesis is often associated. It is essential to choose the length and position of the fusion according to the pelvic incidence and global alignment of the patient. It is possible to add interbody fusion to the posterolateral arthrodesis to improve graft area and stability, increase local lordosis and open foramina. The most common surgical treatment for DS is posterior decompression with instrumented fusion. Nevertheless, some cases are more complicated and it is crucial to consider the patient's general health status, symptoms and alignment when selecting the surgical strategy. Cite this article: EFORT Open Rev 2018;3 DOI: 10.1302/2058-5241.3.170050